Intestinal Intussusception Associated with Cloacal Protusion in Trachemys scripta elegans - Zafalon da Silva, Bruna; Formenton, Bruna Dinah; Schmidt, Victória Regina de Queiroz; do Santos, Eduardo Almeida Ruivo; Alievi, Marcelo Meller (Acta Scientiae Veterinariae, 2021)
Background: Gastrointestinal dysfunction in reptiles is a common condition seen in animal medicine, and is often caused by inappropriate husbandry. The purpose of this report is to describe the case of a surgical procedure for enterectomy of the small intestines, performed as treatment for an intussusception with cloacal protrusion that occurred in a red-eared slider (Trachemys scripta elegans) kept as a pet. Case: A 20-year-old red-eared slider (Trachemys scripta elegans) was taken into medical care after the owner’s observation of a cloacal protrusion that had started 72 h previously. During physical examination the protrusion was noted as an intestinal segment of approximately 5 cm, which was not reducible. Complementary examinations, including radiography and hematological profiling, were performed and revealed no significant findings; therefore, it was decided that an exploratory celiotomy would be conducted. The patient was referred to the surgical unit for the procedure and underwent surgical anesthesia. After appropriate antisepsis of the surgical area, a plastron osteotomy was performed using a previously sterilized oscillatory saw at a 45º angulation. The celomatic membrane was subsequently incised to enable both cavity and intestinal inspection allowing observation of the intussusception in the small intestine of the animal with the intussuscept segment protruding through the cloaca. The intussusception was undone, and an enterectomy was performed to remove the unviable intestine, using intestinal resection and subsequent anastomosis with simple interrupted sutures using 4-0 nylon, followed by intestinal reposition in the cavity. The celomatic membrane was closed using continuous suture with 4-0 nylon. The plastron fragment was then repositioned with the aid of eight cerclage fixations using 2-0 stainless steel wire. It was subsequently covered in self-polymerizing resin acrylic in order to promote impermeability and to protect the surgical wound. During the recovery period, supportive treatment and analgesia and antibiotic therapy were performed. The patient’s first defecation was observed five days after the procedure, and gastrointestinal tract functions returned to normal after four weeks. In six weeks, the patient was discharged. Discussion: In this case, exploratory celiotomy was performed due to the extension of the necrotic areas of the protruded mucosa. Plastron osteotomy is generally indicated because of the possibility of wide organ exposure. During the long healing period of reptiles, a surgical wound can be a gateway for pathogens that lead to postoperative surgical complications. As such, the use of acrylic resin in the present case was to create a protective barrier that would offer more resistance and impermeability. End-to-end enterectomy, in this instance, proved to be an efficient treatment for the small intestines cloacal protrusion, just as it was for the intussusception that preceded it. The probable cause of this case of intussusception was not well defined, and reptiles kept as pets have several diseases that can affect the gastrointestinal tract. The environment temperature also strongly influences gastrointestinal tract functions, which can lead to motility decline and imbalance of the intestinal flora, followed by the production of gases and toxins by microorganisms responsible for dysfunctions. Inadequate temperature management was the suspected main cause of intussusception in this case, as the patient was kept without access to sunlight or a heating source. In conclusion, the enterectomy with subsequent anastomosis that we performed was successful in the treatment of cloacal protruded intussusception of the small intestines in this red-eared slider (Trachemys scripta elegans).